In Vitro and In Silico Antioxidant Efficiency of Bio-Potent Secondary Metabolites From Different Taxa of Black Seed-Producing Plants and Their Derived Mycoendophytes - Hassane, Abdallah M. A.; Hussien, Saleh M.; Abouelela, Mohamed E.; Taha, Taher M.; Awad, Mohamed F.; Mohamed, Hassan; Hassan, Mohammad M.; Hassan, Mohammad H. A.; Abo-Dahab, Nageh F.; El-Shanawany, Abdel-Rehim A. (Frontiers in Bioengineering and Biotechnology, 2022)
Oxidative stress is involved in the pathophysiology of multiple health complications, and it has become a major focus in targeted research fields. As known, black seeds are rich sources of bio-active compounds and widely used to promote human health due to their excellent medicinal and pharmaceutical properties. The present study investigated the antioxidant potency of various black seeds from plants and their derived mycoendophytes, and determined the total phenolic and flavonoid contents in different extracts, followed by characterization of major constituents by HPLC analysis. Finally, in silico docking determined their binding affinities to target myeloperoxidase enzymes. Ten dominant mycoendophytes were isolated from different black seed plants. Three isolates were then selected based on high antiradical potency and further identified by ITS ribosomal gene sequencing. Those isolated were Aspergillus niger TU 62, Chaetomium madrasense AUMC14830, and Rhizopus oryzae AUMC14823. Nigella sativa seeds and their corresponding endophyte A. niger had the highest content of phenolics in their n-butanol extracts (28.50 and 24.43 mg/g), flavonoids (15.02 and 11.45 mg/g), and antioxidant activities (90.48 and 81.48%), respectively, followed by Dodonaea viscosa and Portulaca oleracea along with their mycoendophytic R. oryzae and C. madrasense. Significant positive correlations were found between total phenolics, flavonoids, and the antioxidant activities of different tested extracts. The n-butanol extracts of both black seeds and their derived mycoendophytes showed reasonable IC50 values (0.81–1.44 mg/ml) compared to the control with significant correlations among their phytochemical contents. Overall, seventeen standard phenolics and flavonoids were used, and the compounds were detected in different degrees of existence and concentration in the examined extracts through HPLC analysis. Moreover, the investigation of the molecular simulation results of detected compounds against the myeloperoxidase enzyme revealed that, as a targeted antioxidant, rutin possessed a high affinity (−15.3184 kcal/mol) as an inhibitor. Taken together, the black seeds and their derived mycoendophytes are promising bio-prospects for the broad industrial sector of antioxidants with several valuable potential pharmaceutical and nutritional applications.